Metode Evaluasi Tipologi Street Front: Studi Kasus: Kembang Jepun, Surabaya - Ruth Aureline Marsha Buwono; Rony Gunawan Sunaryo; Agus Dwi Hariyanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: Street Front Typology Evaluation Method; The Case of Kembang Jepun, Surabaya The Kembang Jepun district is one of the old districts of Surabaya. Located on the banks of the Kalimas River, Kembang Jepun determines the pulse of trading activity in Surabaya. As a vital district in Surabaya, the district needs to maintain its image and vitality in its corridors. The quality of the street front is all the things and activities that occur in city corridors, between buildings and roads. The street front is one of the main factors in determining the image and life of the district. This study aims to determine the street front quality in Kembang Jepun, to identify the parts of the district with the best and worst quality of the street front, and to classify the determining elements of the quality of the street front. This study uses descriptive qualitative method research. The analysis found that the Kembang Jepun district is classified as a district with a low skewed street front quality. Jalan Kembang Jepun corridor, an arterial road for Surabaya City with high connectivity, was found to have the best street front quality. Then, Jalan Kalimas Utara Corridor facing Kalimas River, is the road with the worst street front quality. The determining elements of the quality of the street front include the quality of the building facade, the presence of pedestrian paths, activities in front of the building, building openings, and road connectivity.